2021
DOI: 10.3233/jhd-210500
|View full text |Cite
|
Sign up to set email alerts
|

Huntington’s Disease in Israel: A Population-Based Study Using 20 Years of Routinely-Collected Healthcare Data

Abstract: Background: Huntington’s disease (HD) is a rare, genetic, neurodegenerative disease. Obtaining population-level data on epidemiology and disease management is challenging. Objective: To investigate the epidemiology, clinical manifestations, treatment, and healthcare utilization of patients with HD in Israel. Methods: Retrospective population-based cohort study, including 20 years of routinely collected data from Maccabi Healthcare Services, an insurer and healthcare provider for one-quarter of the Israeli popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…The long follow-up time and complete death recording make this an ideal study to assess mortality in patients with a diagnosis of HD. The median survival time in the AoHD cohort was 12.1 years, which is similar to recent population-based cohort studies of HD in Israel (12 years [42]) and the UK (12.4 years [47]), which also define the index as the first diagnosis in the patient's medical records and take place during a similar time window. Other studies have reported median survival up to 25 years [48][49][50] which may be attributable to the index definition, study methods and accuracy of death reporting.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The long follow-up time and complete death recording make this an ideal study to assess mortality in patients with a diagnosis of HD. The median survival time in the AoHD cohort was 12.1 years, which is similar to recent population-based cohort studies of HD in Israel (12 years [42]) and the UK (12.4 years [47]), which also define the index as the first diagnosis in the patient's medical records and take place during a similar time window. Other studies have reported median survival up to 25 years [48][49][50] which may be attributable to the index definition, study methods and accuracy of death reporting.…”
Section: Discussionsupporting
confidence: 81%
“…Beyond psychiatric medications, we also looked at the prescription of tetrabenazine, a monoamine inhibitor that is currently the only treatment indicated specifically for the treatment of motor abnormalities in HD in Sweden. Only 1% of patients had been prescribed tetrabenazine in the years before diagnosis, which rose to 19% in the years after diagnosis; this was low compared with the incidence of tetrabenazine use in a recent retrospective study in Israel (63%) [ 42 ]. Finally, we also explored the incidence of PEG feeding, a means of bypassing the oral cavity to provide hydration and nutrition directly into the gastrointestinal system, with the hope of reducing complications including pneumonia, malnutrition and immobility.…”
Section: Discussionmentioning
confidence: 99%
“…9 Late-stage HD and long disease duration were associated with more emergency department services and overnight hospitalizations. 9,10 However, Medicare patients with HD in any stage of the disease were more likely to use emergency department services, be hospitalized, and less likely to use office visits. 9 Based on data using the National Inpatient Sample between 2003 and 2010, there has been a linear increase in the number of HD admissions in the United States.…”
Section: Resultsmentioning
confidence: 99%
“…12 Psychiatric disorders, behavioral disturbances, and cognitive impairment are other common causes of hospitalization. 10,12,15,16 Patients with HD are also more likely to be discharged to long-term facilities, and dementia, behavioral disturbances, and psychosocial difficulties are associated with a greater likelihood of long-term placement. 11,12,16 Multidisciplinary approaches such as HD-specialized nursing care and palliative care consultation are associated with a lower length of hospitalization and a lower likelihood of discharge to a long-term facility.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 13 studies were suitable for meta‐analysis (two from North America, one from Asia, and 10 from Europe). Five studies were excluded from the meta‐analysis as they reported incidence in select populations 22,34,36 or did not provide adequate data for the calculation of cases and sample size 10,25 . The pooled incidence calculated from these studies was 0.48 cases per 100,000 person‐years (95% CI, 0.33–0.63; I 2 = 65%; Q = 34).…”
Section: Resultsmentioning
confidence: 99%